Can mandala coloring effectively reduce anxiety and burden in palliative care caregivers? Randomized controlled trial - Baykal, Dilek; Çömlekçi, Necmiye; Fircasiguzel, Ozge; Yılmaz, Mihriban (Routledge Journals, Taylor & Francis Ltd, 2025)
Palliative care units offer holistic support for terminally ill patients and their families, addressing psychological, and social needs to enhance quality of life in the final stage. This study aimed to evaluate the effect of mandala coloring on anxiety and caregiver burden among caregivers in palliative care. Care providers in the intervention group were asked to paint mandala tasks twice a week per month. State-Trait Anxiety Inventory and Zarit Burden Interview Scale were implemented for caregivers in the intervention group (n = 52) and control (n = 53) group at the beginning of the study and after a month. The care burden of caregivers, which was 34.53 +/- 13.04 in the intervention group before the mandala intervention, decreased to 13.78 +/- 11.67 after the intervention (p<0.001). On the other hand, in the control group, the care burden was 36.69 +/- 25.68 at the beginning while it increased to 44.50 +/- 12.01 after one month. Although the anxiety level was 52.03 +/- 6.78 in the intervention group before the intervention, it declined to 44.65 +/- 3.87. In addition, the anxiety level in the control group, which was 57.18 +/- 8.47 before the application, increased to 61.05 +/- 4.60 after one month, and all these results were found to be significantly different (p<0.001). Mandala coloring has positive effects on reducing caregiver burden and anxiety levels in caregivers in palliative care.
Keywords: Palliative care; caregiver; burden; anxiety; coloring